2017
DOI: 10.2147/btt.s136188
|View full text |Cite
|
Sign up to set email alerts
|

<div>Epigenetic memory of oxidative stress: does nephrilin exert its protective effects via Rac1?</div>

Abstract: AimNephrilin peptide, a designed inhibitor of Rictor complex (mTORC2), exerts pleiotropic protective effects in metabolic, xenobiotic and traumatic stress models. Stress can generate enduring epigenetic changes in gene function. In this work we examine the possibility that nephrilin treatment protects against acute and enduring global changes in oxidative metabolism, with a focus on the Rictor-complex-mediated activation of Rac1, a subunit of NADPH oxidase (Nox) via PKCs, Prex1 and p66shc.MethodsGiven the wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…A recent study showed that a severely stressful event (thermal injury) in rats generates enduring epigenetic changes in a pathway associated with mitochondrial oxidative metabolism, the Rac1/NADPH oxidase (Nox) pathway [18]. Markers of oxidative stress, such as 8-isoprostane and other markers of lipid peroxidation, are often elevated in neuroinflammation and CNS dysfunction [19,20].…”
Section: Oxidative Stress: a "Global" Mechanism Of Stress Plasticity?mentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study showed that a severely stressful event (thermal injury) in rats generates enduring epigenetic changes in a pathway associated with mitochondrial oxidative metabolism, the Rac1/NADPH oxidase (Nox) pathway [18]. Markers of oxidative stress, such as 8-isoprostane and other markers of lipid peroxidation, are often elevated in neuroinflammation and CNS dysfunction [19,20].…”
Section: Oxidative Stress: a "Global" Mechanism Of Stress Plasticity?mentioning
confidence: 99%
“…Both PKCs and Prex serve to hyper-activate Rac1. In some studies, nuclear translocation of Rictor appears to control both neuroinflammation and oxidative stress via Rac1 hyper-activation [18,[21][22][23][24].…”
Section: Oxidative Stress: a "Global" Mechanism Of Stress Plasticity?mentioning
confidence: 99%
See 1 more Smart Citation
“…Nephrilin's mechanism of action has previously been shown to involve protection from excessive oxidative stress in kidney. 7 In this study, using quantitative reverse transcriptase polymerase chain reaction (qRT-PCR) amplification of transcripts in total RNA extracted from dorsal root ganglia (DRG) of male rats 14 days after exposure to thermal insult, we query the relative levels of expression of 34 genes believed to be associated with oxidative stress biology in the CNS, with an emphasis on astrogliosis, immunosuppression and mitochondrial homeostasis. These phenomena appear to be inextricably linked to one another, and to CNS oxidative stress post-traumatic insult in a variety of contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Nephrilin’s mechanism of action has previously been shown to involve protection from excessive oxidative stress in kidney. 7 …”
Section: Introductionmentioning
confidence: 99%